Gray Box Coverage Criteria for Testing Graph Pattern Matching - Wieber, Martin; Schürr, Andy (Electronic Communications of the EASST, 2012)
Model transformations (MT) are a core building block of Model-Driven Engineering. The quality of MT specifications and implementations is vital to their success. The well-researched formal underpinning of graph transformation (GT) theory allows for proving quality-relevant properties and enables stringent implementations. Yet, in practice, MT implementations often depend on verification/validation techniques based on dynamic testing. This work presents a new gray box coverage approach for systematic testing of GT-based MT implementations and pattern specifications. The approach uses GT specifics and enforces systematic testing by examining variable binding and unbinding steps, thereby not making further assumptions about the underlying pattern matching algorithm. A family of coverage criteria is defined as temporal logic (LTL) formulae, and the effectiveness of concrete criteria in limiting the testing effort is examined by an example.